The Effect of Partial Defoliation, Leaf Position and Developmental Stage of the Vine on Leaf Chlorophyll Concentration in Relation to the Photosynthetic Activity and Light Intensity in the Canopy of Vitis vinif era L. cv. Cabernet Sauvignon - Hunter, J.J.; Visser, J.H. (South African Journal of Enology and Viticulture, 2017)
The effect of partial defoliation and leaf position on leaf chlorophyll concentration in relation to the photosynthetic activity and light intensity in the canopy of Vitis vinifera L. cv. Cabernet Sauvignon was investigated at berry set, pea size, veraison and ripeness stages. The leaves of the severely defoliated vines appeared to contain the highest chlorophyll concentration. In general, chlorophyll a decreased as the leaves were situated progressively deeper into the canopy. No consistent relationship between chlorophyll concentration, light intensity and photosynthetic activity could be found for the different leaf positions. However, to obtain leaves that photosynthesize optimally, the amount and time of leaf removal in the grapevine canopy must be carefully planned.